1992
DOI: 10.1007/bf02536146
|View full text |Cite
|
Sign up to set email alerts
|

Derivatives of Di‐O‐octanoylglycerol and mono‐O‐octylglycerol as modulators of protein kinase C and diacylglycerol kinase activities

Abstract: Twelve analogs of 1,2-di-O-octanoylglycerol modified at C-3 and three quaternary N-alkyl-ammonium derivatives of glycerol were synthesized. The compounds were tested in vitro as potential modulators of the calcium activated, phospholipid dependent protein kinase C (PKC) and diacylglycerol (DAG) kinase activities in order to understand the molecular interactions of these enzymes with their natural activators, inhibitors, or substrates. PKC activity was assayed by measuring histone H1 phosphorylation, and the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Moreover, DAG was not absolutely essential for activity, but a synergistic activation of enzyme was identified in the presence of PS. In the absence of PS, DAG did not increase the phosphorylation ratio of substrate [2,[20][21][22][23]. Similarly, Figure 2 showed very low phosphorylation ratios in the absence of PS.…”
Section: Phosphorylation Of Peptide Substrate By Recombinant Pkcα αmentioning
confidence: 63%
“…Moreover, DAG was not absolutely essential for activity, but a synergistic activation of enzyme was identified in the presence of PS. In the absence of PS, DAG did not increase the phosphorylation ratio of substrate [2,[20][21][22][23]. Similarly, Figure 2 showed very low phosphorylation ratios in the absence of PS.…”
Section: Phosphorylation Of Peptide Substrate By Recombinant Pkcα αmentioning
confidence: 63%
“…A PS-binding domain is not found in PKCa, but PS shows synergistic activation with DAG and Ca 2þ during phosphorylation. 1,[16][17][18] Our study showed that ATP could be more easily lost than Ca 2þ , DAG or PS during sample preparation.…”
Section: Phosphorylation Of Substrate Peptide By Pkc Isozymesmentioning
confidence: 92%